The stage of development of the Regional Programme on Beans in Eastern Africa - Kirkby, Roger A. (International Center for Tropical Agriculture, 1987)
The organization of the Regional Program on Beans in Eastern Africa is indicated as well as the research and training activities carried out. Germplasm, on-farm, and agronomy research activities have been conducted to support national teams, not in separate field trials. A short-term strategy was the assembly of the African Bean Yield and Adaptation Nursery. Germplasm screening has taken place in Uganda and Ethiopia; both countries will soon release their 1st new bean var. On-farm research in Ethiopia studied farming systems particularly regarding farmer management practices related to weeding; in Uganda, research focussed on advantages and disadvantages of var. mixtures. Agronomy trials in Ethiopia were centered on the intensification of cropping systems (double cropping, relay cropping, simultaneous intercropping of beans with sorghum or maize) in the wetter, cooler areas of the highlands. Regional collaborative research activities covered topics of bean pathology (rust, anthracnose, and common bacterial blight) and the beanfly. The complementarity of much of the bean research in Eastern Africa and in other regions of Africa is evidenced, particularly between Uganda, Rwanda, and Zaire. (CIAT)